2016
DOI: 10.1177/0969733015574925
|View full text |Cite
|
Sign up to set email alerts
|

Chinese nurses’ perceived barriers and facilitators of ethical sensitivity

Abstract: This mixed-methods study showed that even though the Chinese nurses have moderately high sensitivity to the ethical issues encountered in hospitals, there is still room for improvement. The barriers to and facilitators of ethical sensitivity identified here offer new and important strategies to support and enhance the nurses' sensitivity to ethical issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 33 publications
(70 reference statements)
5
64
1
4
Order By: Relevance
“…Our result was similar to the study (7) that reported an alpha Of 0.85. Minor coefficients were reported in the studies that used MSQ as a source of data collection, as evidenced: the Chinese version of MSQ had an alpha of 0.82 (23) ; nurses from Iran 0.78 (20) ; Korean nurses 0.76 (24) and alpha of 0.73 with nursing students (2) .…”
Section: Discussionmentioning
confidence: 99%
“…Our result was similar to the study (7) that reported an alpha Of 0.85. Minor coefficients were reported in the studies that used MSQ as a source of data collection, as evidenced: the Chinese version of MSQ had an alpha of 0.82 (23) ; nurses from Iran 0.78 (20) ; Korean nurses 0.76 (24) and alpha of 0.73 with nursing students (2) .…”
Section: Discussionmentioning
confidence: 99%
“…(3) Ethical sensitivity is linked to practice, being limited by knowledge gaps related to ethics, lack of work experience, hierarchical organizational climate and conformist attitude; differently, positive cultural environments at work enhance such sensitivity. (18) In this analysis, the relationship between greater moral distress among public service professionals, for example, may require that we reflect on real problems and precarious conditions, work teams and quality and safety of care, or on the possibility that work environments and management forms favor reflection and a critical approach to the ends and means of work. Finally, is the suffering due to working in worse conditions or to working with more reflection, discussion, and high qualitative ideals?…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is deemed important to support and stimulate strategies that enhance this competence to improve professionals' sensitivity to ethical problems of their daily work. (1,26) The study had as limitations low participation, and participants' difficulty to express themselves on such a complex issue, which justifies further studies. It is suggested that this result may be associated with insecurity, institutional political issues, and even the feeling of disbelief in the return that an academic study can bring to professional practice, especially when the reported causes refer to issues affecting nursing activities in various contexts, and not just for the study participants.…”
Section: Discussionmentioning
confidence: 99%